COE inhibits vasculogenic mimicry in hepatocellular carcinoma via suppressing Notch1 signaling. (17th August 2017) - Jue, Chen; Min, Zhao; Zhisheng, Zhang; Lin, Cui; Yayun, Qian; Xuanyi, Wang; Feng, Jin; Haibo, Wang; Youyang, Shi; Tadashi, Hisamitsu; Shintaro, Ishikawa; Shiyu, Guo; et al.
Abstract: Ethnopharmacological relevance: Vasculogenic mimicry (VM) has been suggested to be present in various malignant tumors and associated with tumor nutrition supply and metastasis, leading to poor prognosis of patients. Notch1 has been demonstrated to contribute to VM formation in hepathocellular carcinoma (HCC). Celastrus orbiculatus extract (COE), a mixture of 11 terpenoids isolated from the Chinese Herb Celastrus orbiculatus Vine, has been suggested to be effective in cancer treatment. Aim of the study: In the current study, experiments were carried out to examine the effect of COE on VM formation and HCC tumor growth both in vitro and in vivo . Materials and methods: CCK-8 assay and Nikon live-work station were used to observe the viability of malignant cells treated with COE. Cell invasion was examined using Transwell. Matrigel was used to establish a 3-D culture condition for VM formation. Changes of mRNA and protein expression were examined by RT-PCR and Western Blot respectively. Tumor growth in vivo was monitored using in vivo fluorescence imaging device. PAS-CD34 dual staining and electron microscopy were used to observe VM formation. Immunohistochemical staining (IHC) was used to examine Notch1 and Hes1 expression in tumor tissues. Results: Results showed that COE can inhibit HCC cells proliferation and invasion in a concentration-dependent manner. VM formation induced by TGF-β1 was blocked by COE. In mouse xenograft model, COE inhibited tumor growth and VM formation. Both in vitro and in vivo studies showed that COE can downregulate expression of Notch1 and Hes1. Conclusion: The current results indicate that COE can inhibit VM formation and HCC tumor growth by downregulating Notch1 signaling. This study demonstrates that COE is superior to other anti-angiogenesis agents and can be considered as a promising candidate in HCC treatment. Graphical abstract: